Research and Practice on the System of the Transformation from Basic Art Theory Courses to Application-oriented Courses - Du, Lijun (Journal of Theory and Practice of Contemporary Education, 2023)
Based on the new curriculum standards, new goals and new requirements have been put forward for talent training. The implementation and implementation of the concept of application-oriented talent cultivation, together with the renewal and development of the concept of art design, has become the focus of the art school's research on how to promote the transformation of basic art theory courses to application-oriented ones, realize the fundamental transformation of teaching ideas, and meet the basic requirements of application-oriented talent cultivation. In this regard, the teaching of basic art theory courses should not follow the rules, nor should it be too concerned about application and eager to achieve success. Under the premise of pursuing effective connection with the theoretical courses, systematic basic training should be realized.